The new method of determination of harmonic parameters and coefficients of pulsations of nonsinusoidal processes - Красноусова, О. Ю. (Problems of Informatization and Control, 2009)
The method has been developed for calculation of spectrum densities of impulses and the coefficients of pulsations of periodical series of impulses. The distinctive feature of this method is the calculation of the required parameters without integrating by Fourier or Laplace